Forensic Analysis of Damage in Malaysia Government Structural Assets: Case Studies from JKR Reports - Sallehuddin Shah Ayop (International Journal of Integrated Engineering, 2025)
The Public Works Department (PWD)’s primary roles include conducting forensic investigations into structural failures and recommending detailed corrective and preventive measures. It also serves as an expert advisory body, providing expert advice and assessments on structural forensics issues to other government departments and agencies. The department ensures the safety and integrity of government assets through expert forensic analysis and guidance. The research objective is to identify the causes of damage to government-owned structures using forensic reports from the PWD Forensic Division. The scope is focused on forensic reports issued specifically by the PWD building’s forensic team. Published forensic reports from the PWD Forensic Division were assessed. The research involved identifying and analysing the findings from these reports to determine the variables associated with damage to different building structures. The data was compiled, conceptualised, and statistically analysed to explore correlations between damage factors. There is a notable increase in the number of forensic reports produced each year. Based on the research results, several variables contribute to the structural damage of government buildings. The most frequently observed factor is material deterioration. An in-depth analysis indicates that cracks in the building structure are a primary cause of material deterioration. These cracks often occur alongside other forms of damage such as delamination, spalling, and corrosion. The conclusion drawn from this research is that the number of forensic examination applications for government buildings is likely to increase. The prevalence of cracks found in the majority of forensic reports indicates significant structural changes that are often only visible through detailed examination. This highlights the need for meticulous attention from all technical stakeholders involved in design, project monitoring, and maintenance. Addressing these issues proactively is essential to ensure the structural integrity and longevity of government buildings.